Katherine . The Ballad of Andy Crocker - Spacek, Sissy; Winkler, Henry; Majors, Lee; Heatherton, Joey (Dollar Entertainment, 2004)
Katherine/The Ballad of Andy Crocker are two classic drama movies and was released Feb 22, 2005 by the Mill Creek Entertainment studio.